2007
DOI: 10.1161/01.res.0000258468.31815.42
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Abnormal Calcium Homeostasis in Mutations Responsible for Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: Abstract-Catecholaminergic polymorphic ventricular tachycardia is a heritable arrhythmia unmasked by exertion or stress and is characterized by triggered activity and sudden cardiac death. In this study, we simulated mutations in 2 genes linked to catecholaminergic polymorphic ventricular tachycardia, the first located in calsequestrin (CSQN2) and the second in the ryanodine receptor (RyR2). The aim of the study was to investigate the mechanistic basis for spontaneous Ca 2ϩ release events that lead to delayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…Although Mg 2+ may affect several ion channels, Mg 2+ inhibition of RyR2 channel activity (24, 35-37) appeared to be sufficient to account for its beneficial effects on CASQ2-deficient myocytes. A recent simulation model of CPVT similarly supported this conclusion: addition of other currents (e.g., the sodium-Ca 2+ exchanger) was unnecessary to recapitulate experimental data (38). In CASQ2-deficient mice, Mg 2+ also significantly decreased the frequency of catecholamineinduced sustained ventricular arrhythmias ( Table 2).…”
Section: Tablementioning
confidence: 74%
“…Although Mg 2+ may affect several ion channels, Mg 2+ inhibition of RyR2 channel activity (24, 35-37) appeared to be sufficient to account for its beneficial effects on CASQ2-deficient myocytes. A recent simulation model of CPVT similarly supported this conclusion: addition of other currents (e.g., the sodium-Ca 2+ exchanger) was unnecessary to recapitulate experimental data (38). In CASQ2-deficient mice, Mg 2+ also significantly decreased the frequency of catecholamineinduced sustained ventricular arrhythmias ( Table 2).…”
Section: Tablementioning
confidence: 74%
“…The general mechanism (besides stretch) has been assumed to be based on an intracellular Ca 2ϩ storage (endoplasmic reticulum) rapidly unloading its content into the cytosolic space, while reuptake has shown a much longer time constant, making the system prone to selfsustained intracellular Ca 2ϩ oscillations. Despite the large number of experimental results, and the range of mathematical models available, only a limited number of modeling studies have been conducted to reproduce DADs based on biophysical mechanisms (24,34,64,81). Using 37 mathematical models of atrial, Purkinje, and ventricular cells of various species, we found that 23 of them could be used to reproduce DADs (see Table 3).…”
Section: Ca 2ϩ Oscillations and Reduction Of Ncxmentioning
confidence: 99%
“…Mathematical models (Shannon04 and Iyer07) have been used in the past to confirm the principal plausibility of this hypothesis (34,81), but alternative mechanisms were not quantitatively assessed. Our results show that both of these models can be used to reproduce DADs in the absence of a dependence of the RyR open probability on Ca SR levels (see Table 3 and Fig.…”
Section: Ca Sr Modulates the Appearance And Determines The Amplitude mentioning
confidence: 99%
See 1 more Smart Citation
“…The models include representation of the main mechanisms of ionic transport across the cell membrane and between subcellular compartments. From a mathematical point of view, the models typically consist of systems of ordinary differential equations (ODEs), with the most detailed ones (such as Iyer et al (2007)) having over 60 ODEs. These models allow representation of the effect of mutations, drugs and disease on ion channel function.…”
Section: Computational Cardiac Electrophysiologymentioning
confidence: 99%